Desarrollo de algoritmos de medición de puntos significativos de amplitud y tiempo en los trazos ECG utilizando índices de fusividad - Villa A, Carlos; Reyna C, Marco Antonio; Villa A, Rafael (Revista Mexicana de Ingenieria Biomedica, 2004)
This paper presents the development of algorithms that use the fuzziness index in order to measure significant time’s periods and amplitude points in consecutive ECG signals. The main of them adjust a threshold to detect the presence or absence of a QRS complex. This threshold is treated as a fuzzy threshold because it depends on health’s patient characteristics. In other words, with difficult quantification through discrete reasoning. This algorithm is complemented with the proposal of criterions to help in the detection of the real existence of the Q and S waves. In this work, we propose a modification of the tracking windows to find the P and T waves proposed by Laguna Lasosa4. We converted the window in a function depending on the fuzziness index of each ECG signal. This due to the variation of the electrocardiogram components which have a great dependence on the rhythm and the relative deformation between them. These algorithms and criterions were probed using 80 ECG signals (forty real signals from a Holter register and forty created artificially).